Epidemic Shocks and Civil Violence: Evidence from Malaria Outbreaks in Africa - Cervellati, Matteo; Esposito, Elena; Sunde, Uwe (The Review of Economics and Statistics, 2022)
This paper presents the first systematic investigation of the effect of epidemic shocks on civil violence. The identification exploits exogenous within cell × year variation in conditions that are suitable for malaria transmission using a panel database with month-by-month variation at a resolution of 1∘×1∘ latitude/longitude for Africa. Suitable conditions increase civil violence in areas with populations susceptible to epidemic outbreaks. The effect is immediate, related to the acute phase of the epidemic and largest during short harvesting seasons of subsistence crops. Genetic immunities and antimalaria policies attenuate the effect. The results deliver new insights for prevention and attenuation policies and for potential consequences of climate change.